Epistle In Indo–Anglian Literature: a Critical Evaluation With Special Reference to Jawaharlal Nehru’S Writing: Jawaharlal Nehru: The Hidden Teacher in His Epistles (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Nehru has converted his gaol into an open university anddispatched lessons through epistles on a variety of topics ranging from the“Alphabet of Nature” to tumultuous, significant events pertaining to battles,revolutions and allied topics. I wish to call him the harbinger and precursorof Modern Distance Education. His epistles reveal the concealed teacher in hispersonality, apart from being a statesman and a poet in politics.